Modifications of the non-linear parameters of the heart rate variability related to the systematic practice of physical exercise - González-Velázquez, Víctor Ernesto; Rebustillo-Escobar, Roxana María; Semanat-Gabely, Walfrido; Cobiellas-Carballo, Lázaro; Sánchez-Hechavarría, Miguel Enrique (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: In recent years the relationship between the systematic practice of physical exercise, cardiovascular dynamics and the functioning of the autonomic nervous system has been recognized. Objective: To determine the modifications that nonlinear parameters undergo in the autonomic cardiovascular regulation of the heart rate variability with the systematic practice of physical exercise. Methodological Design: Retrospective cohort analytical study in the period from February 2016 to August 2018. Universe and sample of 36 individuals (Group 1: 18 high performance baseball athletes, Group 2: 18 students from the University of Medical Sciences of Santiago de Cuba). The data were collected in the Biomedical Basic Sciences Laboratory of the University’s Faculty 1, through the 8-channel PowerLab polygraph, and stored using the Kubios Software version 3.0.4 Premium. Results: Statistically significant differences were found in heart rate values (p = 0.000); SD1 (p = 0.025); SD2 / SD1 ratio (p = 0.007); sample entropy (p = 0.011); short-term fluctuations alpha 1 (p = 0.019); linear average length (p = 0.016); linear maximum length (p = 0.001); recurrence rate (p = 0.034); determinism (p = 0.010) and Shannon entropy (p = 0.015). The parameters of SD1 (C = 906) and sample entropy (C = 712) were significantly associated with a heart rate ≤ 70 beats / min. Conclusions: With the systematic practice of physical exercise, the non-linear dynamics of the autonomic cardiovascular regulation of the heart rate variability undergoes modifications that respond to a better adaptability of the autonomic nervous system, and to a greater capacity to regulate cardiovascular function.